A Critical Analysis of Holmes's Theory of Torts - Patrick J. Kelley (Washington University Law Quarterly, 1983)
In this Article I will first attempt to describe Holmes's theory of torts in a sufficiently broad context to reveal his methodology, the assumptions underlying his methodology, and the relation between Holmes's methodology and his substantive theory. After placing Holmes's theory within the philosophical tradition of nineteenth-century positivism, I shall attempt a practical critique of Holmes's methodology by analyzing its assumptions, the reasonableness of these assumptions, and the matters the methodology is forced to conclude are irrelevant. I then focus on Holmes's substantive theory to see whether it is internally coherent in light of these methodological assumptions. The analysis concludes by isolating the novel theoretical concepts introduced by Holmes to explain tort liability. This work is a preliminary to further theorizing about tort liability. It is purely critical and analytical.
Keywords: Torts; United States; Oliver Wendell Holmes Jr.